Analisis Pengaruh Inflasi Pangan, Pendapatan Per Kapita, dan Tingkat Kemiskinan Terhadap Ketahanan Pangan di Indonesia Tahun 2019-2023 - Nurul Latifah; Tuty Sariwulan; Siti Nurjannah (Indo Publishing, 2026)
This study aims to examine the effect of food inflation, per capita income, and poverty on food security across 34 provinces in Indonesia during the 2019–2023 period. A quantitative approach was employed using panel data regression analysis with the Fixed Effect Model (FEM). The study utilized secondary data obtained from the National Food Agency and Statistics Indonesia. The partial analysis indicates that food inflation has a negative but insignificant effect on food security. This finding suggests that rising food prices tend to reduce people's access to food; however, the impact is not statistically significant. This result is consistent with global evidence showing that increases in food prices may exacerbate food insecurity, although in Indonesia the impact appears to be mitigated by food price stabilization policies and social protection programs. Per capita income has a negative and significant effect on food security. This finding indicates that increases in average income have not been distributed evenly across the population, thereby limiting their contribution to improving overall food security. In contrast, the Food Poverty Line has a positive and significant effect on food security, indicating that greater purchasing power to meet the minimum food requirement of 2,100 kcal per capita per day contributes to improved food security. This result is consistent with previous studies showing that a substantial proportion of the population in developing countries has not yet achieved the minimum recommended calorie intake. Simultaneously, food inflation, per capita income, and the Food Poverty Line have a significant effect on food security, with a coefficient of determination of 90.48%. These findings suggest that improving food security requires comprehensive policies focusing on food price stabilization, a more equitable distribution of income, and expanded access to food for vulnerable populations in a sustainable manner.